EFFECT OF SAFETY VALVES AND HOLE DIAMETER STOVE AGAINST BIOGAS FLAME - Harie Satiyadi Jaya; Jhonni Rentas Duling (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
Problem of rural communities in Indonesia is difficult to obtain kerosene on the market. Team researchers have tried to provide a solution by building a biogas digester type "dome" in the Tuwung village as a model, but this effort has a new problem that the resulting biogas digester quickly run out. From the results of the investigation are diagnosed digester output pipe clogged by water causing increased pressure and temperature so that the process of formation of biogas disturbed and also not optimum biogas stove hole so wasteful. To obtain the solution of this problem, this study aims: 1) Designing and making a safety valve digester; 2) Designing the optimum pit stove; 3) Creating pressure gauge digester. The method used in this research is true experimental research. the results of this study were: 1) A safety valve made from plastic bottles with a capacity of 2 liters, and filled with water to a depth of 6 cm, so it can withstand the pressure of the digester to 100.58 atm.2) Diameter hole obtained optimum stove is 6.5 mm; 3) Pressure gauge manometer water digester is made of transparent plastic hose diameter of 6 mm.